Geografia da dominação: um estudo sobre a organização espacial da terra do sal (Macau-RN) - Carmo Júnior, João Batista (2006)
This work aims to understand the spatial organization in the Town of Macau, State of Rio Grande do Norte, Brazil. This approach focus on bringing back the history of the town, the main personages responsible for the construction of this place, denominated "social agents", as well as its social processes and the spatial forms derived from them. As the personages and their practices were identified, it was found out the existence of a driving force for structuring, interlocking, and maintaining the actions carried out by the social agents during the time. Such actions were materialized in the urban space: "the social segregation". The social segregation takes place as a specific geography of domination. The outcome of those owning the best areas" and ways of accessibility in the urban space, varies from the enrichment by property valorization, because of the concentration of public investments of infrastructure, to the comfort of easily reaching all the daily needs related to the displacements in the urban space. In the latter case, such facility has contributed to improve life quality. While one takes advantage of the location in the urban space, others are negatively affected by the same process. This research identified the salina worker as the weakest element of this social structure, occupying the urban periphery of the town of Macau. Such area is characterized by the lack of services and urban equipment in opposition to the center of the town, the locus of elite. This way, it is established the most known segregation pattern: center x periphery, in which the space acts as a mechanism of segregation